Studi Pemenuhan Air Baku Dengan Metode Penurapan Dan PAH Oleh Masyarakat Pulau Palue-NTT - Mauritius I. R. Naikofi; Egidius Kalogo; Sebastianus B. Henong; Paulus Sianto; F.Wahyu Kristono (Universitas Katolik Soegijapranata, 2020)
The program to meet the needs of Raw Water for the domestic needs of the community, especially drinking water and other household needs, is very intensively carried out by the provincial government of East Nusa Tenggara. The difficulty faced is that efforts to equalize the fulfillment of the need for clean water in the archipelago require quite expensive costs and technology. Palue Island in Sikka Regency is one of the islands of hundreds of regions experiencing a clean water crisis. Fulfillment of consumption water needs only comes from the results of the Steam Water Condensation using plaster and PAH methods. This research was conducted to determine the feasibility and contribution of the fulfillment of residents' raw water by the anointing method that has been carried out by the Palue Island people for generations.